Shortening the Time Interval for the Referral of Patients With Soft Tissue Sarcoma to Expert Centers Using Mobile Health: Retrospective Study - Simon Nannini; Nicolas Penel; Emmanuelle Bompas; Thibault Willaume; Jean-Emmanuel Kurtz; Justine Gantzer (JMIR Publications, 2022)
BackgroundAccording to guidelines, all patients with sarcoma must be managed from initial diagnosis at expert sarcoma centers. However, in everyday practice, the time interval to an expert center visit can be long, which delays presentation to an expert multidisciplinary tumor board and increases the risk of inappropriate management, negatively affecting local tumor control and prognosis. The advent of mobile health offers an easy way to facilitate communication and cooperation between general health care providers (eg, general practitioners and radiologists) and sarcomas experts. We developed a mobile app (Sar'Connect) based on the algorithm designed by radiologists from the French Sarcoma Group. Through a small number of easy-to-answer questions, Sar'Connect provides personalized advice for the management of patients and contact information for the closest expert center. ObjectiveThis retrospective study is the first to assess this mobile app's potential benefits in reducing the time interval for patient referral to an expert center according to the initial clinical characteristics of the soft tissue tumor. MethodsFrom May to December 2021, we extracted tumor mass data for 78 patients discussed by the multidisciplinary tumor boards at 3 centers of the French Sarcoma Group. We applied the Sar'Connect algorithm to these data and estimated the time interval between the first medical description of the soft tissue mass and the referral to expert center. We then compared this estimated time interval with the observed time interval. ResultsWe found that the use of Sar'Connect could potentially shorten the time interval to an expert center by approximately 7.5 months (P<.001). Moreover, for half (31/60, 52%) of the patients with a malignant soft tissue tumor, Sar'Connect could have avoided inappropriate management outside of the reference center. We did not identify a significant determinant for shortening the time interval for referral. ConclusionsOverall, promoting the use of a simple mobile app is an innovative and straightforward means to potentially accelerate both the referral and management of patients with soft tissue sarcoma at expert centers.